Plasma of Argon Treatment of the Implant Surface, Systematic Review of In Vitro Studies - Massimo Carossa; Davide Cavagnetto; Francesca Mancini; Alessandro Mosca Balma; Federico Mussano (Biomolecules, 2022)
This paper aims to review the evidence of the cellular activity on titanium samples exposed to Plasma of Argon (PoA) treatment. A systematic review was carried out based on the PRISMA statement by searching the Cochrane Library, PubMed, Web of Science, EMBASE and Scopus, up to October 2020. Papers were selected according to PICOS format that is: Population (P): osteoblasts, fibroblasts, gingival cells; Intervention (I): PoA disinfection treatment; Comparison (C): untreated controls; Outcome (O): cell culture; Setting (S): in vitro assays. The quality assessment was performed according to the CRIS Guidelines (Checklist for Reporting In vitro Studies). A total of 661 articles were found, of which 16 were included. The quality assessment revealed an overall poor quality of the studies analyzed. In vitro studies on the potential of PoA showed a potential effect in promoting higher cell adhesion and protein adsorption in the earliest times (hours). This outcome was not so evident when later stages of cell growth on the surfaces were tested and compared to the control groups. Only one study was conducted in vivo on a human sample regarding abutment cleaning. No meta-analysis was conducted because of the variety of experimental settings, mixed methods and different cell lines studied. PoA seems to be effective in promoting cell adhesion and protein adsorption. The duration of this effect remains unclear. Further evidence is required to demonstrate the long-term efficacy of the treatment and to support the use of PoA treatment in clinical practice.